Mapping the patterns of wireless village internet service usage among rural communities - Omar, Siti Zobidah; Bolong, Jusang; Alby, Jeffrey Lawrence D'Silva; Mohamed Shaffril, Hayrol Azril (Medwell Journals, 2016)
This study attempts to determine the patterns of Wireless Village Internet services among rural communities in Malaysia. This quantitative study used a developed questionnaire as the main data-collection instrument. A total of 400 villagers from the four districts in Malaysia were selected as the respondents. The analysis reveals that most of the respondents are new users of the service; however, most of them are considered heavy users. Understandably, the respondents use wireless village services for three main purposes, namely web surfing, seeking the latest information (politics, crime, sports, current issues) and social media. A number of discussion points are highlighted and it is hoped that this will act as a basis for strategy development among concerned parties so as to further enhance the quality of wireless village services.